Development of an experimental system to investigate the interaction between the Helicoverpa armigera stunt virus capsid protein and viral RNA - Nel, Andrew James Mascré (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
Tetraviruses are entomopathogenic viruses that propagate solely in lepidopteran hosts. Viruses of this group possess non-enveloped 38- to 40-nm capsids arranged in T = 4 surface symmetry. The viral genome consists of one or two single stranded positive sense RNA strands, which define the two genera of this family, the monopartite betatetraviruses and the bipartite omegatetraviruses. Two extensively studied members of the tetraviruses are the omegatetraviruses, Helicoverpa armigera stunt virus (HaSV) and the closely related Nudaurelia capensis Ï‰ virus (NÏ‰V). The larger genomic strand of HaSV (RNA1) encodes the viral replicase, while the other (RNA2) encodes the 71-kDa capsid precursor protein (p71). The pro-capsid is assembled from 240 copies of p71, which undergo a maturation auto-catalytic cleavage into the 64-kDa (p64) capsid protein and a 7-kDa peptide (p7) forming the capsid shell. The mechanism for the recognition and packaging of the viral genome is poorly understood for these viruses. The principle objective of the research described in this study was to develop in vitro and in vivo experimental systems to investigate interactions between the N terminal domain of HaSV p71 and viral RNAs. More specifically, the two positively charged clusters of predominantly arginine residues that are conserved amongst tetraviruses and the structurally analologous nodaviruses capsid protomers' N terminal domains were investigated. An in vitro RNA-protein "pull down" system was developed using the rapid protein purification technique of the IMPACTTM-CN system. The coding sequence of the N terminal domain of p71 was fused to that of a chitin binding affinity tag (intein). This fusion protein was used as protein bait for the viral RNA. It was proposed that if RNA interacted with the fusion protein, it would be pulled down by the mass of affinity matrix and be precipitated and fluoresce when analysed by agarose gel electrophoresis using ethidium bromide. Despite optimisation of the in vitro assay, results were affected by the interaction between the intein-tag and nucleic acids, the state of the expressed fusion protein (in particular self-cleavage) and the excessive fluorescence present on the gels. The ADH2-GAPDH yeast expression system was used to investigate the in vivo assembly of p71 containing deletions of either one or both clusters within N terminal domain. It was found that all p71 mutants were expressed with the exception of the mutant containing a deletion of the second cluster. The reasons for this still require further investigation. The expressed p71 mutants were not processed into p64 and were degraded in vivo. In addition, an experimental attempt to purify assembled p71 mutant VLPs was unsuccessful. The assembly defect of p71 mutants emphasised the significance of the clusters, which are possibly required for interaction with viral RNAs for efficient VLP assembly. The results of this study suggest that an alternative tag or in vitro RNA-protein interaction assay be used. In addition, further experiments are required to investigate whether the co-expression of full length viral RNAs are required to rescue the in vivo assembly defect of p71 mutants into VLPs.
Keywords: Helicoverpa armigera; RNA viruses